Exhibition of Novel Photocatalytic Activity and Photoluminescence Properties with High Inhibition Towards Bacterial Growth by Hydrothermally Grown ZnO Nanorods - Sahu, Dojalisa; Panda, Nihar R. (Current Nanoscience, 2021)
Background: Metal oxide nanomaterial such as ZnO shows novel structural, optical, electrical and antibacterial properties due to its wide bandgap (3.37 eV) and high excitonic binding energy (60 meV). Probing these inherent properties of nanosized ZnO with different morphologies has generated new interest among researchers. Objective: To investigate the size-dependent functional attributes, ZnO nanorods were prepared by hydrothermal method and the photocatalytic (PC) efficiency was studied. The photoluminescence (PL) property of ZnO nanorods was also studied by recording the emission spectrum under photoexcitation. These nanorods (NRs) were coated on cotton fabric to study the effectiveness of these NRs in defending and inhibiting the growth of different bacteria. Methods: The crystallographic structure and morphology of the ZnO samples were investigated by X-ray diffraction (XRD) and field emission scanning electron microscopic (FESEM) measurements. PL measurement at room temperature was undertaken by exciting the sample with light of wavelength 350 nm. The PC property of ZnO NRs was studied in degrading organic dyes like methylene blue. Bacteria like Staphylococcus aureus, Escherichia coli and Bacillus subtilis were cultured and the inhibition of growth of these bacteria was studied by the application of ZnO. To enhance the microbe defence mechanism of fabric, we coated these NRs on fabric test samples and investigated the bacterial growth on it. Results: XRD and FESEM studies reveal the dimension of the synthesized products in the nano range. These nanorods are of high density and have surface roughness as per the FESEM study. PL measurement shows the presence of strong UV emission at 382 nm with defect emissions in the bluegreen region opening up the path for ZnO to be used in the fabrication of optoelectronic devices. PC study reveals that 89% degradation of methylene blue (MB) dye is achievable in 180 min using these ZnO catalysts. The anti-bacterial study shows that the minimum inhibitory concentration (MIC) of ZnO nanorods coated on the fabric against S. aureus is found to be 3.5 mg/ml which is the minimum as compared to E. coli (7.5 mg/ml) and B. subtilis (5.5 mg/ml). The study further enunciates that fabric coated with ZnO samples exhibited considerably high inhibition activity towards S. aureus. Conclusion: The study shows that ZnO NRs can be effectively used for the fabrication of UVLASER/ LED. The photocatalytic efficiency of ZnO will be useful for the degradation of organic dyes controlling environmental pollution. It further enunciates that fabric coated with ZnO samples exhibited considerably high inhibition activity toward S. aureus (skin bacteria) which will be helpful in defending microbes if used in surgical cotton bandages.
Keywords: photocatalysis